“You’re only a carrier” – women and the language of haemophilia - Chaplin Steve; Khair Kate (The Journal of Haemophilia Practice, 2021)
Women who have the gene variant for haemophilia are labelled solely as ‘carriers’ unless they have a factor VIII activity of ≤40%. This term, which describes an individual who can pass on a disorder but are themselves unaffected, reflects a legacy that extends from the 18th century to the present day. There is strong evidence that women labelled as carriers experience heavy periods, joint damage, pain and impaired quality of life. The label ‘carrier’ does not recognise this burden and is associated with guilt, stigma and difficulty accessing care. People living with a long-term disorder should now be described using person-first terminology and it is common to see the term ‘people with haemophilia’. The term ‘carrier’ should be limited to its application in genetics and not used as a catch-all label for women with haemophilia.